Kaifiyat - Aditya Basu (Dastavezi, 2022)
This film looks to explore experiences of reminiscence, haunting, and confusion, of the Kashmiri Pandit community, vis-a-vis Kashmir, the place considered by the migrant community, a lost home. I look to examine questions of the community's recent loss of agency, assimilation, and angst, from the vantage point of my own transferred inheritance of this experience. The resultant short film, written and made on a shoe-string student-film budget, is I hope ultimately an intriguing rabbit-hole leading into recent Kashmiri Pandit history.